Teacher's Encouragement Factor Influencing EFL Students' Willingness to Communicate in Speaking Class - Syukri, Suhartini; Haseng, Husnul Fahimah; Halim, Abdul (AL LUGHAWIYAAT, 2022)
This case study investigates the teacher’s encouragement factor influencing EFL students’ willingness to communicate in a speaking classroom context. The data in this study involved five EFL students from the English Education Department at a higher education institution in South East Sulawesi who were recruited based on their participation in the speaking class. Data were collected using the reflection of five EFL students and an online interview as a follow-up instrument to dig deeper into the data. The data were thematically analyzed using. Therefore, the researcher used the thematic analysis, then color-coding and categorized based on the willingness to communicate (WTC) framework. The findings indicate that students' WTC in speaking class is closely related to the four factors influencing the teacher's wait time, error correction, support, and teacher’s strategy as encouragement elements. Students with self-motivation acknowledged being more encouraged and confident to communicate in the classroom context. This study suggests future research can be conducted with many participants.Keywords: case study; L2 speaking class; teacher encouragement; willingness to communicate.